Antibody persistence upto 5 years after primary immunization and booster with an inactivated chromatographically purified Vero cell-derived Japanese encephalitis vaccine in Thai children - Hattasingh W. (2023)
Japanese encephalitis is the main cause of viral encephalitis in Asia. In a previous single-arm vaccine trial, an inactivated chromatographically purified Japanese encephalitis Vero cell vaccine (CVI-JE; JEVACTM) was safe and immunogenic in 152 Thai children aged 1–3 years receiving a 2-dose primary immunization and booster dose 1 year later. We conducted a 5-year follow-up assessment of the persistence of the immune response the 144 children remaining in this cohort after first booster dose. Immunity was assessed by 50% plaque reduction neutralization test annually for up to 5 years post-booster. Seroprotection rates (95%CI) decreased from 100% (97.1–100) at 1 year post-booster to 93% (85.0–98.3) at 5 years post-booster. No serious vaccine-related adverse events or Japanese encephalitis infections were reported. A 2-dose primary immunization and booster 1 year later with CVI-JE provided long-lasting immunity in the majority of children.